What the bubble knows: Lake methane dynamics revealed by sediment gas bubble composition. (4th February 2019) - Langenegger, T.; Vachon, D.; Donis, D.; McGinnis, D. F.
Abstract: Atmospheric methane (CH4 ) concentrations have more than doubled in the past ~ 250 yr, although the sources of this potent greenhouse gas remain poorly constrained. Freshwaters contribute ~ 20% of natural CH4 emissions, about half attributed to ebullition. Estimates remain uncertain as ebullition is stochastic, making measurements difficult, time consuming, and costly with current methods (e.g., floating chambers, funnel gas traps, and hydroacoustics). We present a novel approach to quantify basin‐wide hypolimnetic CH4 fluxes at the sediment level based on measurements of bubble gas content and modeling of dissolved pore‐water gases. We show that the relative ebullition flux pathway can be resolved by knowledge of only bubble gas content. As sediment CH4 production, diffusion, and ebullition are interrelated, the addition of a second observation allows closing the entire sediment CH4 balance. Such measurements could include bubble formation depth, sediment diffusive fluxes, ebullition, sediment CH4 production, or the hypolimnetic CH4 mass balance. The measurement of bubble gas content is particularly useful for identifying local ebullitive hotspots and integrating spatial heterogeneity of CH4 fluxes. Our results further revealed the crucial effect of water column depth, production rates, and hypolimnetic dissolved CH4 concentrations on sediment CH4 dynamics. Although we apply the model to cohesive sediments in an anoxic hypolimnion, the model can be applied to shallow, oxic settings by altering the CH4 production rate curve to account for oxidation. Utilizing our approach will provide a deeper understanding of in‐lake CH4 budgets, and thus improve CH4 emission estimates from inland freshwaters at the regional and global scales.